Mental health first aid training for Australian medical and nursing students: an evaluation study. Issue 1 (December 2015) - Bond, Kathy; Jorm, Anthony; Kitchener, Betty; Reavley, Nicola
Abstract Background The role and demands of studying nursing and medicine involve specific stressors that may contribute to an increased risk for mental health problems. Stigma is a barrier to help-seeking for mental health problems in nursing and medical students, making these students vulnerable to negative outcomes including higher failure rates and discontinuation of study. Mental Health First Aid (MHFA) is a potential intervention to increase the likelihood that medical and nursing students will support their peers to seek help for mental health problems. This study aimed to evaluate the effectiveness of a tailored MHFA course for nursing and medical students. Methods Nursing and medical students self-selected into either a face-to-face or online tailored MHFA course. Four hundred and thirty-four nursing and medical students completed pre- and post-course surveys measuring mental health first aid intentions, mental health literacy, confidence in providing help, stigmatising attitudes and satisfaction with the course. Results The results of the study showed that both the online and face-to-face courses improved the quality of first aid intentions towards a person experiencing depression, and increased mental health literacy and confidence in providing help. The training also decreased stigmatizing attitudes and desire for social distance from a person with depression. Conclusion Both online and face-to-face tailored MHFA courses have the potential to improve outcomes for students with mental health problems, and may benefit the students in their future professional careers.